Overexpression of PARP is an independent prognostic marker for poor survival in Middle Eastern breast cancer and its inhibition can be enhanced with embelin co-treatment - Siraj, Abdul Khalid (Oncotarget, 2018)
Patients with aggressive breast cancer (BC) subtypes usually don’t have favorable prognosis despite the improvement in treatment modalities. These cancers still remain a major cause of morbidity and mortality in females. This has fostered a major effort to discover actionable molecular targets to treat these patients. Poly ADP ribose polymerase (PARP) is one of these molecular targets that are under comprehensive investigation for treatment of such tumors. However, its role in the pathogenesis of BC from Middle Eastern ethnicity has not yet been explored. Therefore, we examined the expression of PARP protein in a large cohort of over 1000 Middle Eastern BC cases by immunohistochemistry. Correlation with clinico-pathological parameters were performed. Nuclear PARP overexpression was observed in 44.7% of all BC cases and was significantly associated with aggressive clinico-pathological markers. Interestingly, nuclear PARP overexpression was an independent predictor of poor prognosis. PARP overexpression was also directly associated with XIAP overexpression, with PARP and XIAP co-expression in 15.8% (159/1008) of our cases. We showed that combined inhibition of PARP by olaparib and XIAP by embelin significantly and synergistically inhibited cell growth and induced apoptosis in BC cell lines. Finally, co-treatment of olaparib and embelin regressed BC xenograft tumor growth in nude mice. Our results revealed the role of PARP in Middle Eastern BC pathogenesis and prognosis. Furthermore, our data support the potential clinical development of combined inhibition of PARP and XIAP, which eventually could extend the utility of olaparib beyond BRCA deficient cancer.